Livelihood of Independent Waste Pickers (Tokai) at Dhaka City in Bangladesh: Does it Incidental Choice of them? - Md. Abdul Malak; Sumaiya Fahim Prema; Abdul Majed Sajib; Nahrin Jannat Hossain (Indonesian Journal of Geography, 2022)
The study reveals the status of waste pickers, their livelihood asset profile and the vulnerability due to climatic and anthropogenic factors. It considered the independent waste pickers of Dhaka City, known as Tokai, who collect waste, especially recyclable and reusable materials. Using semi-structured interviews and personal histories, two groups of participants were explored qualitatively: independent waste pickers and other stakeholders. Waste-picking is sometimes the first source of income for persons displaced to Dhaka as a result of human and non-human changes. While most were homeless sheltering anywhere they could, they made a valuable contribution to the recycling industry and to improving environment and ensuring others' well-being, filling a gap left by councils failing to collect the waste produced daily by residents and industry. However, their efforts are largely unrecognized, and their labour stigmatized. Consequently, they have far less access to health, education, credit and utilities. Moreover, poverty and lack of family guidance may make them vulnerable to pursuing involvement in ill-advised political activism. The study concludes that the government and others need to shape a policy that takes into account the livelihood and survival needs of waste pickers and strive to ensure the provision of decent work within this sector and recognition of their societal contribution.